Development of a stability-indicating UPLC method for quantification of mirvetuximab soravtansine-gynx in pharmaceutical formulations using quality by design (QbD) principles - Rao, K. V. Umamaheswara; Shorgar, Neetu (Creative Pharma Assent, 2025)
Background: This study intended to introduce a robust ultra-performance liquid chromatography (UPLC) method for quantifying Mirvetuximab soravtansine-gynx (MSG) in pharmaceutical dosage forms. A systematic approach incorporating the Design of Experiments (DoE) was employed to optimize reliable, sensitive, and efficient chromatographic conditions. Methodology: The finalized method utilized a Waters ACQUITY BEH Phenyl (50 mm) Column with a mobile phase comprising acetonitrile and 0.1% aqueous formic acid in 30:70 (v/v) at 0.2 mL/min and 271 nm and PDA wavelength. Results and discussion: The method validation demonstrates excellent linearity (R² = 0.991, p < 0.05) over 17.50–105 µg/mL. The Intraday and interday precision (%RSD) values were 0.568 and 0.544, respectively, confirming method reproducibility. Accuracy was validated through recovery studies, which produced results within the range of 100.1–100.5%, whereas the robustness test highlights the method's resilience to minor variations. This method detects MSG at a very low concentration of 0.42 µg/mL, confirming method sensitivity. The forced degradation studies were conducted under various stress conditions. The result suggests that moderate degradation of 10.3%, 14.5%, and 9.5 % was noticed in acidic, peroxide, and reduction (9.5%) conditions. Conclusion: The purity analyses confirm the absence of significant impurities in the stress degradation chromatogram, highlighting the stability of MSG and the reliability of the proposed method. In conclusion, the proposed method was rapid, sensitive, precise, robust, and stable for quantifying MSG in pharmaceutical formulations.